Policy trilemma and interest rate behaviour in Nigeria - Korede Ajogbeje; Oluwatosin A. Adeniyi; Festus O. Egwaikhide (CBN Journal of Applied Statistics, 2018)
Policy makers face trade-off in dealing with exchange rate management, mo- netary independence and concerns about capital mobility simultaneously. This study empirically examines the effects of Nigeria's trilemma policy path on interest rate using data spanning from 1997:Q1 to 2017:Q3. It equally incorporates the role of external reserves in buffering these effects. Stationarity of the series were ascertained with Zivot-Andrew (ZA) structural break unit roots test technique, while the bounds test cointegration approach was used to confirm the cointegrating properties of the variables. We found that capital mobility has significant effect on interest rate in the long run base- line model and could also be successfully buffered with external reserves to reduce interest rate. Additionally, our results show that although exchange rate stability and monetary independence do not independently affect interest rate, but their interaction with external reserves does. This implies that external reserve serves as an effective buffer if appropriately employed by the monetary authorities. The trilemma policy can be used to optimally reduce interest rate. Also, external reserves could serve as a tool for economic stabilization with appropriate combination with other relevant policy variables.
Keywords: E4; E6; F4; F41; 330; Capital Mobility; Exchange Rate Stability; Interest Rate; Monetary Independence; Trilemma Policies